Experience with posttransplant lymphoproliferative disorders in solid organ transplant recipients - Nalesnik, Michael A. (1992)
Nearly 6000 solid organ transplants have been performed at the University of Pittsburgh since 1981. Posttransplant lymphoproliferative disorders (PTLD) have occurred in 131 patients, at a frequency of 2.2%. The majority of cases manifest within 6 months following allograft, but individual lesions may arise several years thereafter. From 1981 to 1989, cyclosporine-A (CsA) served as the primary immunosuppressant in this population. In March of 1989, FK506 was introduced for clinical trials. Since that time, 1421 patients have received FK506 either for primary immunosuppression or as rescue therapy. The frequency of PTLD in this subpopulation is 1.5%. PTLD arising under FK506-containing regimens have clinicopathologic features similar to those arising with CsA immunosuppression. The frequency of PTLD at this point in time is approximately 1% in kidney allograft patients, 2.7% in liver, 3.3% in heart and 3.8% in heart/lung or lung recipients. An understanding of the range of histologic appearance is important for the diagnosis of PTLD, especially when it involves the allograft itself. Immunoglobulin heavy chain gene analysis shows that lesions with no rearrangements or with a rearrangement in only a small proportion of cells are more likely to respond to reduced immunosuppression than are those with clonal rearrangement involving a high proportion of cells. However, this distinction is not absolute, and a trial of reduced immunosuppression appears to be indicated regardless of clonal status.